Наш китайский бизнес: роман и рассказы / Дина Рубина - Рубина Дина Ильинична (Эксмо, 2006)
Экземпляры: аб. (ретро) / Инвентарный номер: 41871 / Цена: / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: Р 82 / ББК: 84(2Рос=Рус)6